Union 1812 the Americans who fought the Second War of Independence - Langguth, A. J. 1933- (New York Simon & Schuster, 2006)
In the second and final war of independence, Madison leads an unprepared nation into a struggle that will establish the United States as a major world power and stake its claim to the entire continent. Before the outcome is decided, the war will have engulfed land and sea, with a disastrous U.S. defeat at Detroit and epic naval campaigns on the Great Lakes. After the Americans sack Toronto, the British retaliate by burning the White House and the Capitol. Finally, two and a half years of bloodshed and botched strategies culminate in the spectacular battle of New Orleans. We also meet colorful characters from America's past: not only James and Dolley Madison, but also Sam Houston, Davy Crockett, Oliver Perry, Stephen Decatur, the great Shawnee chieftain Tecumseh, and four men who will follow Madison into the White House--James Monroe, William Henry Harrison, John Quincy Adams, and war hero Andrew Jackson. --From publisher description.
UCASM-1341 (UCASM001341)
Includes bibliographical references (p. 447-463) and index.
Keywords: United States -- History -- War of 1812.; United States -- History -- War of 1812 -- Influence